Does broadband internet allow cities to 'borrow size'? Evidence from the Swedish labour market. Issue 9 (1st September 2020) - de Vos, Duco; Lindgren, Urban; van Ham, Maarten; Meijers, Evert
ABSTRACT: Borrowed size refers to the idea that small cities near larger metropolitan centres can reap the advantages of large agglomerations, but without the costs of agglomeration. The study explores whether broadband internet helps such smaller cities to enjoy the labour market benefits of a larger city. Using Swedish micro-data from 2007 to 2015, together with unique data on broadband, suggestive evidence is found that broadband indeed allows smaller cities to reap such benefits. Borrowed size is primarily driven by the overall penetration of broadband in the place of residence, rather than by broadband availability at the residence.